Effect of various levels of bromochloromethane and fibre level on in vitro methane production and fermentation pattern - SIROHI, S K; GOEL, NAVNEET (The Indian Journal of Animal Sciences, 2013)
An in vitro study was conducted to investigate the effect of bromochloromethane (BCM) on methane production andfermentation characteristics in the 12 treatment combinations prepared by using the 3 levels of fibre (HF,MF,LF) and 4levels of BCM (0, 4, 8 and 12 Î¼M). BCM reduced total gas and methane production (>98% of control) in a dosedependentmanner. In vitro dry matter digestibility (IVDMD) in different treatment combinations were more or less not adversely affected by BCM but found increased in most of the cases with total mixed diet containing wheat straw and berseem as a roughage source. Acetate concentration was also reduced while, percentage of propionate and butyrate was found increased. Acetate : propionate (A : P) ratio was reduced by BCM addition in all treatment combinations. On the basis of present study 4 mM dose of BCM seems to be effective in methane reduction without affecting other rumen fermentation parameters adversely.